METHODS OF FORMATION OF COMMUNICATION IN THE DEVELOPMENT OF CHILDREN’S SPEECH - Siddikova Gulnoza Sharaviddinovna; Zoirova Maharram Yoqubovna; Atamuradova Jamila Begmurodovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the pedagogical features of the process of speech development in preschool children, methods of developing communication activities in children. For modern and full development of speech, interaction with the people around is based on the need to enrich the structure of the child’s need for communication.